2008
DOI: 10.1017/s1355617708081034
|View full text |Cite
|
Sign up to set email alerts
|

Use of MMPI-2 to predict cognitive effort: A hierarchically optimal classification tree analysis

Abstract: Neuropsychologists routinely rely on response validity measures to evaluate the authenticity of test performances. However, the relationship between cognitive and psychological response validity measures is not clearly understood. It remains to be seen whether psychological test results can predict the outcome of response validity testing in clinical and civil forensic samples. The present analysis applied a unique statistical approach, classification tree methodology (Optimal Data Analysis: ODA), in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The source data did not satisfy the assumptions underlying analytical methods that are based on the general linear model or maximum likelihood function ( Grimm & Yarnold, 1995 , 2000 ). Accordingly, all analyses used optimal discriminant analysis, an exact, non-parametric statistical method ( Arozullah et al, 2003 ; Belknap et al, 2008 ; Nebeker et al, 2007 ; Smart et al, 2008 ) to model ED, low libido, and PED. Use of these non-parametric methods simplifies and standardizes presentation and interpretation of statistical findings, avoids certain ambiguities that arise with alternative multivariable analytic methods, ensures valid p -values, and also identifies models that maximize predictive accuracy (i.e., as opposed to models that maximize explained variation or that maximize the value of the likelihood function; Grimm & Yarnold, 1995 , 2000 ; Linden & Yarnold, 2016a , 2016b , 2016c , 2016d , 2016e ; Linden, Yarnold & Nallamothu, 2016 ; Yarnold & Soltysik, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…The source data did not satisfy the assumptions underlying analytical methods that are based on the general linear model or maximum likelihood function ( Grimm & Yarnold, 1995 , 2000 ). Accordingly, all analyses used optimal discriminant analysis, an exact, non-parametric statistical method ( Arozullah et al, 2003 ; Belknap et al, 2008 ; Nebeker et al, 2007 ; Smart et al, 2008 ) to model ED, low libido, and PED. Use of these non-parametric methods simplifies and standardizes presentation and interpretation of statistical findings, avoids certain ambiguities that arise with alternative multivariable analytic methods, ensures valid p -values, and also identifies models that maximize predictive accuracy (i.e., as opposed to models that maximize explained variation or that maximize the value of the likelihood function; Grimm & Yarnold, 1995 , 2000 ; Linden & Yarnold, 2016a , 2016b , 2016c , 2016d , 2016e ; Linden, Yarnold & Nallamothu, 2016 ; Yarnold & Soltysik, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Logistic regression illustrated that the combination of FBS and RBS accounted for the maximum variance in group membership and optimally classified 85.3% of subjects. Smart et al (2008) used classification tree methodology to examine the ability of the standard MMPI-2 validity and clinical scales, additional MMPI-2 validity scales and indices, and an earlier 41-item version of the RBS (Gervais, 2005) to predict cognitive effort in a sample of 307 individuals seen in either a secondary gain context (n ϭ 198) or nonsecondary gain setting (n ϭ 109). Their results revealed that the RBS was used first in classification of cognitive effort, followed by Hysteria.…”
Section: Development Of the Rbsmentioning
confidence: 99%
“…Highly elevated conversion V profiles in particular have been correlated with SVT failure (Boone & Lu, 1999;Larrabee, 1998;Smart et al, 2008). With respect to the MMPI-2 validity scales, the FBS (Lees-Haley, English, & Glenn, 1991) has proven particularly useful for identifying exaggeration or feigning of physical symptoms and disability (Greiffenstein, Fox, & Lees-Haley, 2007) and is closely associated SVT failures (Larrabee, 1998;Nelson, Sweet, Berry, Bryant, & Granacher, 2007;Nelson, Sweet, & Demakis, 2006).…”
Section: Mmpi-2 In Forensic Traumatic Brain Injury Settingsmentioning
confidence: 99%